Private provider practices and incentives for hypertension management in rural and peri-urban Telangana, India– a qualitative study - Samriddhi S Gupte; Ashish Sachdeva; Aman Kabra; Bhanu Pratap Singh; Ashish Krishna; Anupam Khungar Pathni; Bhawna Sharma; Andrew Moran; Amarendar Reddy Mamindla; Nanda Kishore Kannuri; Sarang Deo (BMC Health Services Research, 2024)
Abstract Hypertension poses a critical threat to health in India, being the predominant risk factor for mortality and disability. With over 70% of outpatient care being provided by the private sector, our study investigated the practices and incentives of private health providers in screening, diagnosing, treating, monitoring, and counseling hypertension patients in rural and peri-urban India. Conducted from April 2020 to February 2021, the qualitative study involved 46 participants, including various healthcare professionals and patients in three Telangana state districts. Analysis revealed a lack of recognition of hypertension’s gravity among private providers in these areas, leading to inconsistent screening practices and varied diagnostic thresholds, particularly among rural medical practitioners. Both formal and informal providers lacked standardized protocols and follow-up mechanisms, with limited technical knowledge about hypertension observed, especially among rural practitioners who were often the first point of contact. Drug effectiveness, and incentives from pharmaceutical sales representatives influenced prescribing practices. Diagnostic labs also offered financial incentives for patient referrals. Thus, aligning providers’ objectives with patient preferences and public health goals is crucial. To encourage evidence-based hypertension care, the government and NGOs could implement strategies such as tailored incentives, financial rewards, tax benefits, accreditation, and recognition for private healthcare providers. Professional bodies in the private sector should establish programs emphasizing quality assurance and certifications. Future research should focus on designing and testing new models for private sector hypertension service delivery, coupled with targeted interventions to enhance care in rural and peri-urban settings.